2020
DOI: 10.1021/acsomega.9b04010
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hydrogenation of Aqueous Furfural Using a Metal-Supported Activated Carbon Monolith

Abstract: Continuous hydrogenation of aqueous furfural (4.5%) was studied using a monolith form (ACM) of an activated carbon Pd catalyst (∼1.2% Pd). A sequential reaction pathway was observed, with ACM achieving high selectivity and space time yields (STYs) for furfuryl alcohol (∼25%, 60–70 g/L-cat/h, 7–15 1/h liquid hourly space velocity, LHSV), 2-methylfuran (∼25%, 45–50 g/L-cat/h, 7–15 1/h LHSV), and tetrahydrofurfuryl alcohol (∼20–60%, 10–50 g/L-cat/h, <7 1/h LHSV). ACM showed a low loss of activity and metal leachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
(119 reference statements)
0
14
0
Order By: Relevance
“…As noted in Figure , our STYs for FA (143 g/Lcat/h or 1089 g/kg-cat/h) and THFA (272 g/Lcat/h or 574 g/kg-cat/h) approach these values, indicating possible industrial viability. It is possible that STYs could be increased by increasing the FUR feed rates and optimizing the H 2 gas and liquid flow rates to generate a Taylor flow in the carbon monoliths (our calculations in the past work under the conditions employed in this work indicate that we were in film flow) . The Taylor flow regime could increase the H 2 mass transfer and allow one to process higher FUR concentrations or feed rates. , …”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…As noted in Figure , our STYs for FA (143 g/Lcat/h or 1089 g/kg-cat/h) and THFA (272 g/Lcat/h or 574 g/kg-cat/h) approach these values, indicating possible industrial viability. It is possible that STYs could be increased by increasing the FUR feed rates and optimizing the H 2 gas and liquid flow rates to generate a Taylor flow in the carbon monoliths (our calculations in the past work under the conditions employed in this work indicate that we were in film flow) . The Taylor flow regime could increase the H 2 mass transfer and allow one to process higher FUR concentrations or feed rates. , …”
Section: Resultsmentioning
confidence: 91%
“…Each monolith structure has a diameter and length of 1 in, 529 cells/in 2 , a wall thickness of 0.01 in, a cell spacing of 0.0435 in, a geometric surface area of 70.84 in 2 /in 3 , and an open frontal area of 0.593 in 2 . Details on the ACM production procedure and pictures of ACM have been previously published. Four cores of ACM were loaded into a Parr Packed Bed Reactor System (details have been previously described). ACM catalysts were reduced for 4 h prior to the reaction in the 100 mL/min flow of pure hydrogen at 250 °C. Next, aqueous FUR hydrogenation reactions were conducted at liquid flow rates of 0.5 to 16 mL/min, temperatures of 120–180 °C, and pressures of atm to 300 psig using a feedstock of 44 g/L FUR (purchased from Sigma-Aldrich, 99%) dissolved in DI water.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent study of the kinetics of furfural hydrogenation [ 74 ] showed that ( I ) forms from both ( VII ) and ( II ). Similar palladium catalyst on monolithic active carbon gives up to 10 wt % of (I) in water at 180°С [ 75 ].…”
Section: Synthesis From Renewable Raw Materialsmentioning
confidence: 99%